Effect of Chandrasoor (Lepidium sativum) supplementation on performance of crossbred sows along with nursing piglets - G.P. LAKHANI, BISWAJIT ROY (Indian Journal of Animal Production and Management, 2019)
The present study was conducted at Pig Farm, Livestock Farm, Adhartal, College of Veterinary Science & A.H., NDVSU, Jabalpur. A total of 14 crossbred sows (Large white yorkshire X Desi) just after farrowing were randomly assigned to two different groups (Control and Chandrasoor), with seven sows in each group. Individual sows along with piglets were maintained at farrowing pen. All the sows were fed the same gestation diet during gestation. Diets were formulated as per ICAR (2013) standard. After the farrowing, sows of the Chandrasoor group received 30 g Chandrasoor seed powder daily. Rest of the managemental schedule was same for both the groups Piglets were weaned at 42 days of age. Significant differences (P<0.05) in feed intake (kg/day) between the groups were observed in 28th and 42nd days of lactation. However, feed intake (kg/day) was non-significantly higher in Chandrasoor group. Overall body weight losses (kg) were significantly (P<0.05) higher in the control group. Weaning-to-estrus interval was significantly (P<0.05) lower in the Chandrasoor group in comparison to the control group. Litter size at birth was 9.80±0.56 and 10.12±0.68, respectively for the control and Chandrasoor groups and not varied significantly. Litter size at weaning was 8.00±0.51 and 8.52±0.68, respectively for the control and Chandrasoor groups. Average birth weight (kg) of piglet was 1.55±0.13 and 1.51±0.11, respectively for the control and Chandrasoor groups and not varied significantly. However, weaning weight (kg/piglet) was significantly (P<0.05) higher in Chandrasoor group (7.57±0.42) in comparison to the control group (6.52±0.31). Average daily body weight gain (g/day) of piglets was significantly (P<0.05) varied between the groups and values are 148.10±9.45and 161.91±8.58, respectively for the control and Chandrasoor groups. Pre-weaning piglet mortality was 18.37% in the control group and 15.81% in Chandrasoor group. From the result it can be concluded that supplementation of Chandrasoor improved reproductive performance of sows by reducing body weight loss and days of weaning-to-estrus, improve average weight of piglets at weaning.